Comparisons of Interfacial Phe, Tyr, and Trp Residues as Determinants of Orientation and Dynamics for GWALP Transmembrane Peptides - Sparks, Kelsey A; Gleason, Nicholas J; Gist, Renetra; Langston, Rebekah; Greathouse, Denise V; Koeppe, Roger E (Biochemistry (Easton), 2014)
Aromatic amino acids often flank the transmembrane alpha helices of integral membrane proteins. By favoring locations within the membrane–water interface of the lipid bilayer, aromatic residues Trp, Tyr, and sometimes Phe may serve as anchors to help stabilize a transmembrane orientation. In this work, we compare the influence of interfacial Trp, Tyr, or Phe residues upon the properties of tilted helical transmembrane peptides. For such comparisons, it has been critical to start with no more than one interfacial aromatic residue near each end of a transmembrane helix, for example, that of GWALP23 (acetyl-GGALW5(LA)6LW19LAGA-[ethanol]amide). To this end, we have employed 2H-labeled alanines and solid-state NMR spectroscopy to investigate the consequences of moving or replacing W5 or W19 in GWALP23 with selected Tyr, Phe, or Trp residues at the same or proximate locations. We find that GWALP23 peptides having F5, Y5, or W5 exhibit essentially the same average tilt and similar dynamics in bilayer membranes of 1,2-dilauroylphosphatidylcholine (DLPC) or 1,2-dioleoylphosphatidylcholine (DOPC). When double Tyr anchors are present, in Y4,5GWALP23 the NMR observables are markedly more subject to dynamic averaging and at the same time are less responsive to the bilayer thickness. Decreased dynamics are nevertheless observed when ring hydrogen bonding is removed, such that F4,5GWALP23 exhibits a similar extent of low dynamic averaging as GWALP23 itself. When F5 is the sole aromatic group in the N-interfacial region, the dynamic averaging is (only) slightly more extensive than with W5, Y5, or Y4 alone or with F4,5, yet it is much less than that observed for Y4,5GWALP23. Interestingly, moving Y5 to Y4 or W19 to W18, while retaining only one hydrogen-bond-capable aromatic ring at each interface, maintains the low level of dynamic averaging but alters the helix azimuthal rotation. The rotation change is about 40° for Y4 regardless of whether the host lipid bilayer is DLPC or DOPC. The rotational change (Δρ) is more dramatic and more complex when W19 is moved to W18, as Δρ is about +90° in DLPC but about −60° in DOPC. Possible reasons for this curious lipid-dependent helix rotation could include not only the separation distances between flanking aromatic or hydrophobic residues but also the absolute location of the W19 indole ring. For the more usual cases, when the helix azimuthal rotation shows little dependence on the host bilayer identity, excepting W18GWALP23, the transmembrane helices adapt to different lipids primarily by changing the magnitude of their tilt. We conclude that, in the absence of other functional groups, interfacial aromatic residues determine the preferred orientations and dynamics of membrane-spanning peptides. The results furthermore suggest possibilities for rotational and dynamic control of membrane protein function.